Analisis Kekuatan Struktur Lokal Haluan Drillship 35000 ton Akibat Beban Slamming dengan Pendekatan Metode Elemen Hingga - Mahasin Maulana Ahmad (POLITEKNIK NEGERI BENGKALIS, 2024)
Drillship is a floating structure that functions as a drill that can move from one point to another. The movement of the drillship from one point to another will cause a spectral response. With a certain speed, the spectral response that occurs in the drillship will cause the slamming phenomenon. This journal aims to determine the strength of the local structure at the bow of the 35000 ton drillship due to slamming loads. The analysis is carried out using the finite element method. The loads used in this analysis are dynamic loads of shear forces and bending moments that occur in the local structure of the bow at the FP station by adding forces due to pressure slamming. The analysis of the ultimate strength of the structure is based on ASTM 897 and ASTM A852 metal materials. The results of the analysis show that the local structure at the bow of the drillship collapses at a significant wave height (Hs) of about 11 m, which is 716 MPa for the ASTM A852 metal material type.